Home Truths? : Video Production and Domestic Life. - Buckingham, David; Pini, Maria; Willett, Rebekah (Ann Arbor : University of Michigan Press, 2011)
An academic approach to the popular use of video production technology.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books